2015
DOI: 10.15252/embr.201439882
|View full text |Cite
|
Sign up to set email alerts
|

DCC functions as an accelerator of thalamocortical axonal growth downstream of spontaneous thalamic activity

Abstract: Controlling the axon growth rate is fundamental when establishing brain connections. Using the thalamocortical system as a model, we previously showed that spontaneous calcium activity influences the growth rate of thalamocortical axons by regulating the transcription of Robo1 through an NF-jB-binding site in its promoter. Robo1 acts as a brake on the growth of thalamocortical axons in vivo. Here, we have identified the Netrin-1 receptor DCC as an accelerator for thalamic axon growth. Dcc transcription is regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Altogether these results suggest a mechanism in which an activity-dependent regulation of Rorβ might control the expansion and plasticity of cortical areas by modulating TCA branching. Interestingly, an analysis of the Rorβ promoter identified several motifs that are putative targets for Ca 2+ sensitive transcription factors like CREB, AP-1 and NF-κB-binding sites 41 55 56 . In addition to the effects on Rorβ expression, calcium waves are transmitted to the thalamocortical terminals providing a patterned form of activity that may also contribute to shape different sensory cortical territories.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether these results suggest a mechanism in which an activity-dependent regulation of Rorβ might control the expansion and plasticity of cortical areas by modulating TCA branching. Interestingly, an analysis of the Rorβ promoter identified several motifs that are putative targets for Ca 2+ sensitive transcription factors like CREB, AP-1 and NF-κB-binding sites 41 55 56 . In addition to the effects on Rorβ expression, calcium waves are transmitted to the thalamocortical terminals providing a patterned form of activity that may also contribute to shape different sensory cortical territories.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have previously indicated that NETRIN1, by binding to and activating NETRIN1 receptors such as 'Deleted in Colorectal Cancer' (DCC), plays an important role in commissural and cortical axon guidance (15). More recently, DCC was identified as playing a crucial role in thalamic axonal growth, confirming that interaction of NETRIN1 with DCC leads to successful axon growth during central nervous system development (16). GWAS of other traits related to MDD have also shown an aggregation of variants in the NETRIN1 pathway (17; 18).…”
Section: Introductionmentioning
confidence: 95%
“…[16][17][18] More recently, it was reported that neuronal activity plays a central role in regulating the expression of NT-1 receptor DCC. 19 However, whether neuronal activity regulates NT-1 expression is still unknown. In this study, we regulated striatal neuronal activity through optogenetics to investigate whether the changes in striatal neuronal activity could influence NT-1 expression, neurogenesis and the recovery after ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%